Peran Lembaga Fatwa Wilayatul Faqih dalam Negara Islam Iran - Putri Amanah; Khoerul Anwar (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
The Islamic State of Iran is an Islamic state that adheres to Syiah and makes it a mazhab that must be followed by the entire Muslim community of Iran. This indicates the very strong influence of the Syiah sect in the country, so it is not surprising that the Wilayatul Faqih institution was formed which has an important role in the running of the Iranian state. The decision issued by Wilayatul Faqih is a decision that must be carried out by the government because the fatwa of the scholars contained in the institution is something sacred and cannot be denied so that indirectly the power of the Iranian state is in the hands of the scholars who are in the Wilayatul Faqih because of the large power that the institution has. The Wilayatul Faqih Institute was initiated by Ayatullah Koemaini as an important institution to be formed after successfully changing Iran’s democratic system to an Islamic state that adheres to Syiah. The institution has several functions, including providing fatwas, preserving Islamic law, advancing education, providing direction related to taxes, providing humanitarian services in general, and also many other functions that are the duties and functions of the institution, and the most important thing is serve as supervisors for government agencies.